PERANCANGAN APLIKASI PENJUALAN CCTV PADA PT INTERNUSA TECHNOLOGY DI JAKARTA SELATAN BERBASIS ANDROID - Aditya Yoga Prakasa; Reko Syarif Hidayatullah; Siti Julaeha (Lembaga Pengembangan Kinerja Dosen, 2022)
Watching the rapid development of science and technology, companies that run a sales business are required to be more effective in working and marketing their products. PT Internusa Technology or also known as INUS, is a company engaged in the sale of analog and digital CCTV. PT Internusa Technology has problems in data collection transactions. In addition, there are other problems, there are still very few promotional media to introduce various kinds of products that are to be sold and also prospective buyers sometimes have difficulty in knowing the prices and types of products to be sold by PT Internusa Technology. The purpose of research and making this journal is to make the sales system at PT Internusa Technology computerized, make it easier for PT Internusa Technology to market its products, and also make it easier for prospective buyers to find out the types and prices of products to be sold by PT Internusa Technology. The research method used is Research and Development (R&D). The result is making of applications design that support all the problems discussed previously. This application can make it easier for users to make CCTV sales transactions, the company can market their own products to be sold online with a larger target market, and making it easier for buyers and sellers to transact or just look for information about the store.